ASSOCIATION BETWEEN POLYMORPHISM IN CYTOTOXIC T LYMPHOCYTE ANTIGEN -4 GENE AND THE RISK OF RHEUMATOID ARITHRITIS IN IRAQI PATIENTS - A. A., Rawaa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
CTLA4 is well known that it is expressed in activated T-lymphocyte, and can be distinguished in cancer phenomena as well as many chronic diseases. This study was designed aiming to find a correlation between CTLA-4 and Rheumatoid Arthritis (RA). This research was carried out at Baghdad Teaching Hospital, Medical City, Baghdad, Iraq. In this study, 245 patients diagnosed with rheumatoid arthritis and 188 healthy volunteers’ individuals (control group) were selected randomly. The diagnosis of the RA to both patients group and healthy individuals were characterized according to a certain protocols. The sequence of four (JO31, CT60, +49, and MH30 genotypes) were carried out using PCR-DGGE. The polymorphisms (SNPs) were genotyped for the control and the patients and the distribution of the genotypes was carried out according to HWE (P<0.05) for the two groups. The effect of two alleles on the susceptibility of RA, were investigated thoroughly, and there was a major association between the CT60, +49 alleles with the risk of RA (OR 1.43, 95%Cl (1.14-1.89), and the P-value 0.004 for CT60), while for +49 it was (OR 1.38, 95%Cl (1.04-1.77) and the P-value 0.009). There is a significant correlation between CTLA-4 genes and Rheumatoid Arthritis (RA) and both CT60 and +49 can be the main reason for RA, while JO31 and MH30 are not associated with CTLA-4.